OPTIMALISASI PENDIDIKAN NEUROSAINS BAGI SEKOLAH DASAR - ahmad taufik taufik (Abtadi : Jurnal Pendidikan Dasar, 2022)
Absolute education in human life, because when it will shape the character process. This cannot be separated from the cooperation of teachers and parents. Parents as the first teacher, the formation of character is the essence of the obligation not only carried out from birth, but also the baby is still in the womb. In addition, special teachers at the elementary school level have the same kinds of obligations when it comes to character building. In the process, the teacher uses an approach from brain-based character education (neuroscience). The reason is that this success began with the way the teacher changed the brains of some students. If brain-based character education is implemented from an early age, the implications are that Indonesian education is of higher quality and is able to prepare a quality golden generation. This research uses qualitative based on literature review. Based on the results of the study it was found that quality education is an educational tendency capable of creating perfect character for various students. Character education is more effective when the brain (neuroscience) approach is applied in the school environment, because changing character begins with the principle of brain ability in students.